ANALISA PENENTUAN URUTAN PRIORITAS PEMELIHARAAN JALAN DI KABUPATEN LANDAK PROVINSI KALIMANTAN BARAT DENGAN MENGGUNAKAN PROSES HIRARKI ANALITIK - Widyo Wiyono; Slamet Widodo; Siti Mayuni (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
The road network tends to decrease the conditions indicated by the occurrence of damage to the road. Road maintenance program should be carried out by local governments. With so many obstacles and problems, such as budget constraints, proposed that people continue to enter the Public Works Department, will require planning road network maintenance program to determine the order of priority maintenance This research was conducted in order to analyze and get an order of priority for road maintenance. In this study conducted at three (3) existing roads in Landak District namely roads Sp. Aur-Agak-Sebangki, Sebadu-Karangan roads and road Darit-Ladangan-Sompak is using various criteria. To determine the order of priority road maintenance used method Analytical Hierarchy Process (AHP). Analytical Hierarchy Process is an issue that will be resolved in a frame of mind that is organized, thus allowing can be expressed to take effective decisions on the issue. Criteria were influential in determining the order of priority road is the road conditions, traffic volume, and land use policies. By using Analytical Hierarchy Process, the order of priority road maintenance in Porcupine District based on the value of the highest weight to the lowest weighting is road Sebadu-Karangan 41.0% by weight of the first priority because it has the highest weight. Further road Darit-Ladangan-Sompak is 31.6% by weight, and the final sequence is roads Sp. Aur-Agak-Sebangki with a 27.4% weighting. Keywords: Road Maintenance, Landak District, Analytical Hierarchy Process,Priority Order